Folk Pedagogical Wisdom and Its Reflections in the Literary Works - Vasiliauskas, Romas (Acta Paedagogica Vilnensia, 1997)
In Lithuanian folk pedagogics two periods are distinguished: the pre Christianity and post Christianity (1375) periods. In the first period the educational practice of a peasant child was naturalistic, closely connected with nature and based upon oral traditions and customs. Children learned from work experience and the natural situations of peasant life. In the post Christianity period the first books in Lithuanian language were printed (M. Mažvydas). Due to the influence of printed books in the native language the functions of the oral tradition changed and folk wisdom spread in a short time. Folk traditions of education had been considered by Lithuanian historians and ethnographers (L. Jucevičius, S. Daukantas, and M. Valančius). Ethnic-cultural heritage had been evaluated in their works. These works dealt with folk wisdom, the peoples' view of the native language, moral education, and traditions in the family. In the XIX century the non-official system of education was based upon ethno-pedagogical ideas and family traditions. The peasant family remains an essential bearer of education and a main holder of Christian and national traditions.
Keywords: folk pedagogy; cultural traditions; traditional education; pedagogical wisdom; ethno-pedagogical ideas